2017
DOI: 10.1161/jaha.116.004961
|View full text |Cite
|
Sign up to set email alerts
|

Severe Aortic Stenosis in Dialysis Patients

Abstract: BackgroundCharacteristics and prognosis of hemodialysis patients with severe aortic stenosis have not yet been well defined.Methods and ResultsThe CURRENT AS (contemporary outcomes after surgery and medical treatment in patients with severe aortic stenosis) registry, a Japanese multicenter registry, enrolled 3815 consecutive patients with severe aortic stenosis. There were 405 hemodialysis patients (initial aortic valve replacement [AVR] group: N=135 [33.3%], and conservative group: N=270) and 3410 nonhemodial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…We thus selected 10 clinically relevant factors as the potential risk factors with strong evidence as listed in Table 1 for parsimonious models. This was consistent with our previous report 14 except for the addition of prior myocardial infarction, male sex, body mass index <22, and left ventricular ejection fraction (LVEF). We included LVEF <60% instead of the traditional LVEF <50% as a potential risk predictor because we previously reported that the negative prognostic impact of LVEF 50% to 59% was comparable to that of LVEF <50% in patients with severe AS who were managed conservatively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We thus selected 10 clinically relevant factors as the potential risk factors with strong evidence as listed in Table 1 for parsimonious models. This was consistent with our previous report 14 except for the addition of prior myocardial infarction, male sex, body mass index <22, and left ventricular ejection fraction (LVEF). We included LVEF <60% instead of the traditional LVEF <50% as a potential risk predictor because we previously reported that the negative prognostic impact of LVEF 50% to 59% was comparable to that of LVEF <50% in patients with severe AS who were managed conservatively.…”
Section: Discussionsupporting
confidence: 93%
“…15 As the subgroup analyses, we assessed the cumulative incidence of sudden death in patients with hemodialysis (HD) (N=405) and non-HD patients (N=3410) because we previously reported an extremely high rate of sudden death in HD patients. 14 We also explored the clinical characteristics associated with sudden death in non-HD patients. Statistical analyses were conducted by a physician (T. Taniguchi) and a statistician (T. Morimoto) with the use of JMP 10.0.2 (SAS Institute Inc, Cary, NC) or SAS 9.4 (SAS Institute Inc, Cary, NC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymptomatic patients with a BNP level of <100 pg/mL had a relatively low event rate at 1 year of follow-up, who might be safely followed up with watchful waiting strategy. Finally, in the CURRENT AS registry, HD,46 anaemia47 and tricuspid regurgitation48 were associated with poor clinical outcomes in patients with severe AS.…”
Section: Management Of Asymptomatic Patients With Severe Asmentioning
confidence: 98%
“…The incidence of aortic valve calcification in ESKD nearly doubles that in the general population, and it usually tracks with duration of dialysis (15). Outcomes with severe aortic stenosis in patients on dialysis are worse than those in the general population (35).…”
Section: Valvular Heart Diseasementioning
confidence: 99%